1993
DOI: 10.1073/pnas.90.10.4586
|View full text |Cite
|
Sign up to set email alerts
|

The costimulatory activity of the CD26 antigen requires dipeptidyl peptidase IV enzymatic activity.

Abstract: T cells have been shown to express CD26, a known ectoenzyme with dipeptidyl peptidase IV (DPPIV; EC 3.4.14.5) activity in its extracellular domain. CD26 can also deliver a second costimulatory signal and contribute to T-cell activation. In an earlier study, we established CD26-transfected Jurkat T-cell lines and demonstrated that monoclonal antibody-mediated crosslinking of CD26 and CD3 induced interleukin 2 (IL-2) production. To determine the contribution of DPPIV enzymatic activity to the costimulatory activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
126
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 28 publications
5
126
1
Order By: Relevance
“…CD26 is also involved in T-cell activation, owing to its association with CD45, mannose 6-phosphate/insulin-like growth factor II receptor and adenosine deaminase (ADA) (Morimoto et al, 1989;Dang et al, 1990aDang et al, -d, 1991Torimoto et al, 1991;Kameoka et al, 1993;Morrison et al, 1993;Ikushima et al, 2000). Additionally, its DPPIV enzyme activity has a key role in various aspects of T-cell activation, as demonstrated by studies using DPPIV inhibitors, soluble CD26/DPPIV molecules or CD26 genetic mutants (Flentke et al, 1991;Tanaka et al, 1993Tanaka et al, , 1994Steinbrecher et al, 2001). Besides its involvement in normal T-cell function, CD26 may also have a role in the development of certain tumors (Tanaka et al, 1995;Stecca et al, 1997;Bauvois et al, 1999;Dang and Morimoto, 2002).…”
mentioning
confidence: 99%
“…CD26 is also involved in T-cell activation, owing to its association with CD45, mannose 6-phosphate/insulin-like growth factor II receptor and adenosine deaminase (ADA) (Morimoto et al, 1989;Dang et al, 1990aDang et al, -d, 1991Torimoto et al, 1991;Kameoka et al, 1993;Morrison et al, 1993;Ikushima et al, 2000). Additionally, its DPPIV enzyme activity has a key role in various aspects of T-cell activation, as demonstrated by studies using DPPIV inhibitors, soluble CD26/DPPIV molecules or CD26 genetic mutants (Flentke et al, 1991;Tanaka et al, 1993Tanaka et al, , 1994Steinbrecher et al, 2001). Besides its involvement in normal T-cell function, CD26 may also have a role in the development of certain tumors (Tanaka et al, 1995;Stecca et al, 1997;Bauvois et al, 1999;Dang and Morimoto, 2002).…”
mentioning
confidence: 99%
“…Our recent studies have shown that the DPPIV enzyme activity of CD26 functions to augment cellular responses of CD26-transfected Jurkat cells to external stimuli (13). These studies raise questions as to how CD26 functions in a physiological situation.…”
mentioning
confidence: 99%
“…1, line 2). The small Xba I-Dra III DNA fragment of the mutant CD26 cDNA containing the deletion was substituted for the corresponding DNA fragment of the wild-type CD26 cDNA in the expression vector RcSRa to yield RcSRa-26A3-9 (13). A mixture of RcSRa-26.A&3-9 and pMT-2 (14) providing the dihydrofolate reductase (DHFR) gene was used to transfect a DHFR-deficient CHO cell line, DXB-11, by electroporation (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our present data strongly suggest that persistent NFAT-AP-1 cooperation is responsible for CD26-mediated T cell activation, and sustained activation of NFAT and ERK1/2 is possibly due to the aggregation of signaling molecules in lipid rafts following CD26-mediated costimulation. Furthermore, we have previously shown that DPPIV enzyme activity is partially involved in the costimulatory activity of CD26 through studies using wild-type CD26 (DPPIV + ) or mutant CD26 (DPPIV 2 )-transfected Jurkat T cell lines (55). Other groups reported that the synthetic competitive DPPIV inhibitor Lys[Z(NO 2 )] significantly suppressed the proliferation and production of IL-2, IL-10, and IFN-g in PWM-stimulated human T cells (56).…”
Section: Discussionmentioning
confidence: 99%